Portrayals of suicide and suicide attempts among LGBTQ+ individuals in Indian digital news - Khuman Bhagirath Jetubhai (Dialogues in Health)
This paper examines the nature of Indian digital news reporting on suicides and suicide attempts within the LGBTQ+ community. The objective is to analyse how these incidents are framed by the media by identifying the dominant narratives, demographic characteristics highlighted, and attributed causes presented in news coverage. Following PRISMA guidelines, this study identified and analysed 164 unique digital news reports published between 2001 and 2022. The analysis reveals that news coverage most frequently focuses on individuals identified as trans women or lesbians, who are in the 19–24 and 25–44 age brackets, and are reported to be in a relationship. The most common narratives constructed in these reports attribute the suicides to family non-acceptance of their relationship or identity and partner separation. Furthermore, hanging and drug/poison ingestion are the most frequently reported methods of suicide, and joint/couple suicides are a significant feature of the media coverage. These findings demonstrate that the portrayal of LGBTQ+ suicide in Indian digital media is a curated narrative, likely shaped by journalistic news values rather than being a direct reflection of population-level trends. This research provides critical insights into the construction of media discourse on a sensitive public health issue and its implications for public perception and policy.